ความรู้และความเข้าใจของผู้ทำบัญชีในจังหวัดเชียงใหม่เกี่ยวกับมาตรฐานการรายงานทางการเงินสำหรับกิจการที่ไม่มีส่วนได้เสียสาธารณะ - นภา จันทรา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This independent study aimed at analyzing knowledge and understanding of accountants in Chiang Mai Province towards Financial Reporting Standards for Non-Publicly Accountable Entities. Questionnaires were collected from 342 accountants in Chiang Mai. Data were collected by descriptive statistics which were frequency, percentage and mean. From results of the study, it was found that most of the accountants were female, age 20 to 30 years old, holding Bachelor Degree in Accounting, working for private sectors or companies as accountants, and had 1 to 5 years of work experience. It was found that more than half of the accountants had high to the highest levels of knowledge and understanding towards Financial Reporting Standards for Non-Publicly Accountable Entities. Moreover, the overall point average was at 62.99 percent. Two aspects of knowledge and understanding were measured; first were objectives, conceptual framework and scope of financial reporting standards, and the second were revenue recognition, value measurement, and information presentation and disclosure. Considering point average divided by the positions of accountants, it was found that registered accountants and workers at accounting service offices had medium level on knowledge and understanding about objectives, conceptual framework and scope of financial reporting standards. In addition, they had low level of knowledge and understanding about revenue recognition, value measurement, and information presentation and disclosure. In contrast, freelance accountants had high level of knowledge and understanding about objectives, conceptual framework and scope of financial reporting standards, and had medium level of knowledge and understanding about revenue recognition, value measurement, and information presentation and disclosure. Moreover, if divided accountants in Chiang Mai by their experiences, people who had 1 to 5 years of experiences had low level while people who had over 5 years experiences had medium level of knowledge and understanding about revenue recognition, value measurement, and information presentation and disclosure. Furthermore, most of the accountants in Chiang Mai had problem about knowledge and understanding towards Financial Reporting Standards for Non-Publicly Accountable Entities in the medium level. They had problem about the confusion of financial reporting standards between non-publicly accountable entities and publicly accountable entities, along with regulations for taxable net profit calculation.